Experimental Study on the Heterogeneity of Mechanical Properties of Friction Stir Welded Joints with the Digital Image Correlation Method - Li, H.; Dai, Q.-L.; Shi, Q.-Y. (Проблемы прочности, 2015)
The heterogeneity of mechanical properties of friction stir welded 6082 aluminum butt joints were analyzed with the digital of image correlation (DIC) method. The DIC method provides instantaneous full-field strain distribution data for weld surfaces. Visualized strain field images and local stress–strain curves of weld subzones were derived from these data. The heterogeneity was evaluated by assessing strain concentrations in the strain field images and comparing the constitutive parameters of weld subzones. Furthermore, by comparing these variables of different surfaces of the weld, the potential impact of the mutual constraint between subzone materials on the heterogeneity level was analyzed.. Неоднородность механических свойств стыковых швов алюминиевого сплава 6082, полученных ротационной сваркой трением, анализировали методом корреляции цифрового изображения. Метод обеспечивает получение текущих данных всестороннего распределения деформаций по поверхностям шва. На основании этих данных выполнена визуализация изображений поля деформаций и построена зависимость локальной деформации от напряжения для подзон шва. Неоднородность оценивали путем определения концентрации деформаций на изображениях поля деформаций и сравнения параметров состояния подзон шва. Кроме того, путем сравнения этих параметров для различных поверхностей шва проанализировано возможное воздействие взаимного напряжения материалов подзон на уровень неоднородности.